The Perceptions of Students and Teacher Challenges in Utilizing “Kejar.Id” at One of Vocational School in Serang Regency - Parmana, Asep Eka; Utomo, Dhafid Wahyu; Fargianti, Yusti (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The purpose of this study is to determine student perceptions and challenges faced by a teacher when using Kejar.id during the Covid-19 pandemic. This article uses qualitative descriptive methods with interviews, questionnaires, and documentation techniques to collect data. The data have collected from the twelfth-grade students and the English teacher which have learned using Kejar.id in English subject. The researcher himself is the instrument of this research to analyze the data from participants. The research findings showed that mostly students gave good perceptions about Kejar.id. The students said that the use of Kejar.id helped them in terms of student administration, checking learning progress, accessing virtual classes, the learning process and assessment, meanwhile, the problem experienced by students was the network. Furthermore, the results of interviews conducted with the teacher showed that there are four problems arose in using Kejar.id, namely teaching learning styles and culture challenges, pedagogical e-learning challenges, technological challenges, and time efficiency challenges. The results of this research indicated if students gave the positive perceptions in using Kejar.id also the teacher have faced several challanges when using Kejar.id as learning management system in English classroom